2021
DOI: 10.1016/j.cjco.2021.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal Doppler Ultrasound Renal Venous Stasis Index Correlates With Acute Cardiorenal Syndrome in Patients With Acute Decompensated Heart Failure

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
1
6
1
1
Order By: Relevance
“…A recent study confirmed the prognostic value of discharge IRVF pattern in patients with ADHF [12]. Moreover, a small study showed an association between sonographic parameter of renal venous congestion with creatinine level rise in ADHF [18]. Though there are several similarities with the aforementioned studies such as determined high levels of renal venous congestion parameters in patients with HF, the key differences of the present study is the longitudinal observation analysing the effect of ADHF treatment on IRVF.…”
Section: Discussionsupporting
confidence: 75%
“…A recent study confirmed the prognostic value of discharge IRVF pattern in patients with ADHF [12]. Moreover, a small study showed an association between sonographic parameter of renal venous congestion with creatinine level rise in ADHF [18]. Though there are several similarities with the aforementioned studies such as determined high levels of renal venous congestion parameters in patients with HF, the key differences of the present study is the longitudinal observation analysing the effect of ADHF treatment on IRVF.…”
Section: Discussionsupporting
confidence: 75%
“…7,13 Previous studies had shown that a higher rank IRVF pattern was associated with a poorer prognosis. 8,9,11 However, our study did not yield the same result. This was probably due to the smaller sample size and the different timeline for the secondary endpoints (i.e.…”
Section: Discussioncontrasting
confidence: 68%
“…4,5 An emerging tool of intrarenal venous flow (IRVF) measurement by Doppler ultrasonography was shown to correlate with renal congestion and could aid in the management of DHF with WRF. [6][7][8] However, its clinical implication is yet to be thoroughly defined, and studies on the relationship between IRVF, clinical degree of congestion, other forms of haemodynamic assessment, and renal outcome are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal hepatic venous reflux is the initial manifestation of fluid overload. Several studies have demonstrated that assessing the maximum velocity of the S- and D-waves in the hepatic veins can aid in fluid management decisions [ 47 ]. Changes in the hepatic veins static D-wave during resuscitation of shock are related to volume responsiveness.…”
Section: Clinical Utility Of Vrs In Critically Ill Patientsmentioning
confidence: 99%